Phenolic resin composite material as well as preparation method and application thereof
By adding fumed silica, alumina, mica powder and reinforcing fiber to phenolic resin, a composite material with a specific ratio is formed, which solves the problem of phenolic resin being prone to cracking under high temperature and high pressure, improves the material's high-temperature stability and electrical insulation properties, expands its application range and reduces costs.
Patent Information
- Application Number
- CN202510769341.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-26
AI Technical Summary
Existing phenolic resin materials are prone to significant deformation or cracking under high temperature and high pressure conditions, making them difficult to apply. They also have high preparation costs and poor fluidity, which affects the use of the materials and production efficiency.
By adding fumed silica, alumina, mica powder and reinforcing fibers to phenolic resin, a composite material with a specific ratio is formed to improve its fire resistance, stability and electrical insulation properties, and enhance its tolerance in high temperature and high pressure environments.
The obtained phenolic resin composite material does not crack under flame ablation at 1200°C, is stable under high temperature of 400°C and pressure of 12MPa, has excellent electrical insulation and electrolyte corrosion resistance, expands the scope of application and reduces preparation cost.
Smart Images

Figure BDA0005442553080000131 
Figure BDA0005442553080000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a phenolic resin composite material and a preparation method and application thereof. Background Art
[0002] In fields like petrochemicals and geothermal energy development, materials are exposed to extremely harsh environmental conditions, with temperatures exceeding 300°C and pressures reaching tens to hundreds of bars. These extreme environments place very high demands on material performance. While traditional phenolic resins offer excellent high-temperature resistance, they often struggle to simultaneously withstand high temperatures and high pressures. When pressurized at high temperatures, they often experience significant deformation or even cracking, significantly impacting the material's usability.
[0003] Patent CN110157145A discloses a modified phenolic molding compound with high flexural strength and its preparation method. The raw materials for the modified phenolic molding compound include 200 parts of a thermosetting phenolic resin, 4-6 parts of 2-formyl-3,4-dihydropyran, 3-5 parts of polyvinyl alcohol, 0.2-4 parts of a demolding aid, 7-12 parts of a filler, and 2-3.5 parts of a pigment. The thermosetting phenolic resin is a liquid thermosetting phenolic resin. By adding specific components such as 2-formyl-3,4-dihydropyran and polyvinyl alcohol, the technical problem of reducing the brittleness of the modified phenolic molding compound while decreasing its tensile strength and flexural modulus is overcome, resulting in a modified phenolic molding compound with improved rigidity and toughness.
[0004] Patent CN115819928A discloses a lightweight, high-strength thermal insulation material and its preparation method. The lightweight, high-strength thermal insulation material includes phenolic epoxy resin, epoxy resin, diaminodiphenyl sulfone, tannic acid, hindered phenol antioxidant, silane coupling agent, accelerator, hollow glass microspheres, and solvent. The thermal conductivity of the lightweight, high-strength thermal insulation material provided by this technical solution is 0.1572 W·m -1 K -1 , and can meet the needs of long-term and cyclic heating use under high temperature (200°C) conditions, but its preparation method and curing process steps are complicated.
[0005] CN109486098A discloses a heat-resistant, high-strength phenolic molding compound. The raw materials for the heat-resistant, high-strength phenolic molding compound include 25-26 parts phenolic resin; 1-2 parts modifier; 3-5 parts curing agent; 4-5 parts accelerator; 10-15 parts reinforcing carbon fiber; 0.5-2 parts interfacial modifier; 2-5 parts lubricant; and 10-45 parts inorganic filler. This phenolic molding compound is suitable for manufacturing everyday items such as cookware handles and knobs, and also meets the heat resistance requirements of electronic, electrical, mechanical, and automotive parts. It also offers improved molding process adaptability, enabling both injection molding and compression molding.
[0006] In summary, existing technologies usually only optimize and improve a single property of phenolic resin materials, ignoring the complexity in actual production and application; and none of them solve the technical problem that phenolic resin materials undergo large deformation or even cracking under high temperature and high pressure conditions, making them difficult to use; at the same time, the preparation cost is too expensive, and the material is difficult to level during the manufacturing process due to poor fluidity.
[0007] Therefore, it is of great significance to design and develop a phenolic resin material that does not change the raw material form during the preparation process, has good fluidity, is easy to fill the mold, and is suitable for high temperature and high pressure conditions. Summary of the Invention
[0008] To address the above technical problems, the present invention provides a phenolic resin composite material, its preparation method, and its application. The phenolic resin composite material, based on a phenolic resin matrix and supplemented with specific fillers (mica powder and reinforcing fibers) and reinforcements (fumed silica and aluminum oxide), exhibits excellent fire resistance, excellent stability and durability in high-temperature and high-pressure environments, electrical insulation properties, and resistance to electrolyte corrosion.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a phenolic resin composite material, wherein raw materials for preparing the phenolic resin composite material include phenolic resin, fumed silica, aluminum oxide, mica powder and reinforcing fiber.
[0011] The present invention designs raw materials for preparing the phenolic resin composite material and compounds fumed silica, aluminum oxide, mica powder and reinforcing fibers with the phenolic resin to obtain a phenolic resin composite material with excellent fire resistance. The phenolic resin composite material can withstand flame ablation at 1200°C without cracking or deforming. At the same time, the phenolic resin composite material can remain stable without cracking under a high temperature of 400°C and a pressure of 12MPa. In addition, the phenolic resin composite material also has excellent electrical insulation properties and electrolyte corrosion resistance.
[0012] In the present invention, the addition of fumed silica can change the rheological properties of the phenolic resin and can act as an anti-caking agent for other powders in the system, preventing the powder from settling in the resin. Fumed silica also has excellent high-temperature resistance. The addition of aluminum oxide can improve the flame retardancy and strength of the resulting composite material. The present invention compounding fumed silica with aluminum oxide to create a porcelain-like effect not only reduces economic costs but also enables a synergistic effect between the two, thereby significantly improving the high-temperature pressure-bearing performance of the phenolic resin composite material.
[0013] It should be noted that there is no particular limitation on the type of phenolic resin in the present invention. Any phenolic resin commonly used in the art is applicable, and flame-retardant phenolic resin is preferred.
[0014] Preferably, the mass percentage of the phenolic resin is 45-55%, for example, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% or 55%, based on the total mass percentage of the raw materials for preparation being 100%. The present invention is not limited to the values listed above, and other values not listed within the numerical range are also applicable.
[0015] Within the content range provided in the present invention, the increased content of phenolic resin is conducive to the formation of a carbon layer, which in turn helps to improve its fire resistance so that it does not produce cracks after being burned at high temperatures. However, at the same time, its high-temperature pressure-bearing capacity is reduced. During the production process, it can be selected according to the needs of the actual use scenario.
[0016] Preferably, the fumed silica is hydrophobic fumed silica.
[0017] Preferably, the mass percentage of the fumed silica is 5-15%, for example, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or 14%, based on the total mass percentage of the raw materials for preparation being 100%. The values are not limited to the values listed, and other values not listed within the numerical range are also applicable.
[0018] During the mixing and preparation process of the phenolic resin composite material provided by the present invention, due to the low density of fumed silica, if its content is too high, its compatibility with other components is poor, and it cannot be well dispersed and mixed with other components, which is not conducive to actual production and preparation; if its content is too low, the high-temperature pressure-bearing performance of the prepared phenolic resin composite material is significantly poor.
[0019] Preferably, the mass percentage of the aluminum oxide is 10-25%, based on the total mass percentage of the raw materials being 100%, for example, it can be 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23% or 24%, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable.
[0020] Preferably, the mass ratio of the fumed silica to alumina is 1:(1.5-3), for example, it can be 1:1.5, 1:1.6, 1:1.8, 1:2.0, 1:2.2, 1:2.4, 1:2.6, 1:2.8 or 1:3, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable.
[0021] In the present invention, by optimizing the mass ratio of fumed silica to aluminum oxide, the two can better exert a synergistic effect, thereby making the resulting phenolic resin composite material have good fire resistance and high-temperature pressure-bearing capacity. When the mass ratio of the two is too high or too low, the combination of fumed silica and aluminum oxide will be poor, thereby affecting the porcelainization effect and reducing the high-temperature pressure-bearing capacity of the resulting phenolic resin composite material. Furthermore, when aluminum oxide is not added, the content of fumed silica is too high, resulting in poor compatibility with the various components, which is not conducive to actual production.
[0022] Preferably, the mica powder is a mixture of 300-mesh mica powder and 600-mesh mica powder.
[0023] Preferably, the mass ratio of 300 mesh mica powder and 600 mesh mica powder in the mixed mica powder is (1-2):(0.5-1), for example, it can be 1:0.5, 1:0.8, 1:1, 1.4:0.7, 1.5:0.5, 1.6:0.8, 1.8:0.9, 2:0.5 or 2:1, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable, and more preferably 2:1.
[0024] In the present invention, low-mesh mica powder has a lamellar structure, which makes it have a good fireproofing effect. However, it is prone to uneven mixing when mixed with other components, which in turn affects the film filling effect. By mixing high-mesh mica powder (600 mesh) with low-mesh mica powder (300 mesh) in a specific ratio to obtain a mixed mica powder, it can retain a certain lamellar structure while also being able to be evenly dispersed, not only reducing economic costs, but also improving the high-temperature pressure bearing capacity of the resulting phenolic resin composite material while maintaining good fireproofing properties.
[0025] Preferably, the mass percentage of the mica powder is 5-15%, for example, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or 14%, based on the total mass percentage of the raw materials as 100%. The values are not limited to the values listed, and other values not listed within the numerical range are also applicable.
[0026] In the present invention, when the content of mica powder is too low, the fireproof and heat-insulating properties of the obtained phenolic resin composite material are poor. If the content is too high, the lamellar structure thereof is not conducive to molding, thereby affecting the film filling effect.
[0027] Preferably, the reinforcing fibers include glass fibers.
[0028] In the present invention, the addition of specific reinforcing fibers effectively enhances toughness, thereby reducing the brittleness of the resulting phenolic resin composite. Furthermore, the addition of specific glass fibers (low melting point) allows them to melt with fumed silica and aluminum oxide at lower temperatures (e.g., around 400°C) rather than higher temperatures (e.g., above 1000°C), facilitating vitrification and forming a connected body, thereby increasing the overall material strength.
[0029] Preferably, the length of the glass fiber is 10-15 mm, for example, it can be 10.5 mm, 11 mm, 11.5 mm, 12 mm, 12.5 mm, 13 mm, 13.5 mm, 14 mm or 14.5 mm, without being limited to the listed values, and other unlisted data within the numerical range are also applicable.
[0030] In the present invention, the length of the glass fiber is 10-15 mm, and the comprehensive performance of the obtained phenolic resin composite material is better. If conventional sized short glass fibers (25 mm) are used, their mold filling fluidity is reduced and the film cannot be completely filled, thereby affecting the yield of the obtained product; if the length of the glass fiber used is less than 10 mm, its corresponding toughening effect is poor, and the brittleness of the phenolic resin composite material cannot be improved.
[0031] Preferably, the cross section of the glass fiber includes a circle and / or a square.
[0032] In the present invention, when the cross section of the glass fiber is square, it has a better bulk density, so that the obtained phenolic resin composite material has better high-temperature pressure bearing performance.
[0033] Preferably, the mass percentage of the reinforcing fiber is 5-10%, based on the total mass percentage of the raw materials as 100%, for example, it can be 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 9.5%, without being limited to the listed values, and other unlisted data within the numerical range are also applicable.
[0034] In a second aspect, the present invention provides a method for preparing the phenolic resin composite material as described in the first aspect, the preparation method comprising the following steps:
[0035] The phenolic resin composite material is obtained by mixing phenolic resin, fumed silica, aluminum oxide, mica powder and reinforcing fiber, curing and molding.
[0036] Preferably, the mixing is performed under stirring.
[0037] Preferably, the mixing includes first mixing fumed silica, alumina and mica powder, then adding reinforcing fibers and mixing, and finally adding phenolic resin and mixing.
[0038] Preferably, the curing method includes high temperature curing.
[0039] Preferably, the curing temperature is 150-200°C, for example, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C or 195°C, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable.
[0040] Preferably, the curing time is 1-5 min / mm, for example, it can be 1 min / mm, 1.5 min / mm, 2 min / mm, 2.5 min / mm, 3 min / mm, 3.5 min / mm, 4 min / mm, 4.5 min / mm or 5 min / mm, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable.
[0041] It should be noted that the curing time of 1-5 min / mm means that the curing time is 1-5 minutes per 1 mm thickness.
[0042] Preferably, the forming method includes compression molding.
[0043] Preferably, the molding pressure is 5-10 MPa, for example, it can be 5.5 MPa, 6.0 MPa, 6.5 MPa, 7.0 MPa, 7.5 MPa, 8.0 MPa, 8.5 MPa, 9.0 MPa or 9.5 MPa, and is not limited to the listed values. Other unlisted data within the numerical range are also applicable.
[0044] Preferably, the preparation method of the phenolic resin composite material specifically comprises the following steps:
[0045] (1) Mixing fumed silica, aluminum oxide, and mica powder to form a uniform primary mixture;
[0046] (2) adding reinforcing fibers to the primary mixture described in step (1) and stirring thoroughly to form a secondary mixture;
[0047] (3) adding phenolic resin to the secondary mixture described in step (2) and stirring thoroughly to ensure that the materials are evenly mixed to form a final mixture;
[0048] (4) The final mixture described in step (3) is subjected to a high-temperature curing process at 150-200° C. for 1-5 min / mm and a high-pressure molding process at 5-10 MPa to obtain the phenolic resin composite material.
[0049] In the present invention, in order to ensure the uniformity of mixing, the reinforcing fiber is added after step (1), and the phenolic resin can be added after step (2) or after step (1).
[0050] In a third aspect, the present invention provides a battery pack housing, comprising the phenolic resin composite material described in the first aspect.
[0051] The battery pack housing provided by the present invention comprises a specific phenolic resin composite material, which can effectively isolate the impact of the external environment on the battery and maintain structural integrity when the battery overheats or experiences thermal runaway, thereby preventing high temperature and pressure from damaging the battery module.
[0052] In a fourth aspect, the present invention provides a use of the phenolic resin composite material described in the first aspect in high temperature and high pressure resistant equipment.
[0053] Preferably, the high temperature and high pressure resistant equipment includes equipment in the fields of oil drilling, geothermal wells, aerospace, automobile manufacturing or high-end electronics.
[0054] The phenolic resin composite material provided by the present invention has excellent physical and chemical properties. It can be used in environments with temperatures up to 400°C and can withstand high-temperature flames up to 1200°C for a short period of time without cracking. Furthermore, the phenolic resin composite material remains stable and crack-free in a high-temperature and high-pressure environment of 400°C and 12 MPa. It also maintains excellent physical and chemical stability after continuous exposure to a high temperature of 250°C for 1000 hours. This makes it suitable for use in environments with stringent temperature and pressure requirements, such as petrochemicals and geothermal energy development. This greatly expands its application areas and provides high practicality.
[0055] When the phenolic resin composite material provided by the present invention is used in the field of new energy vehicles, especially in the manufacture of battery pack housings, motors and controller components, its excellent high-temperature and high-pressure resistance can be used to well protect sensitive electronic components and battery cells, thereby ensuring the safety and reliability of the vehicle.
[0056] Compared with the prior art, the present invention has at least the following beneficial effects:
[0057] (1) The present invention optimizes the raw material formula for preparing phenolic resin composite materials. Through the specific combination of phenolic resin, fumed silica, aluminum oxide, mica powder and reinforcing fiber, a phenolic resin composite material with excellent fire resistance and suitable for high temperature and high pressure environment is obtained, which not only reduces the cost of the composite material but also expands its application range.
[0058] (2) The phenolic resin composite material provided by the present invention has excellent heat resistance and fire resistance, can withstand flame ablation at 1200°C, and will not suffer from problems such as cracking and deformation; it can remain stable and not crack under a high temperature of 400°C and a pressure of 12MPa, effectively solving the problem of poor applicability of phenolic resin materials in high temperature and high pressure environments in the prior art; at the same time, it also has excellent electrolyte corrosion resistance and electrical insulation performance. DETAILED DESCRIPTION
[0059] For the convenience of understanding the present invention, the present invention is given below with examples. It should be understood by those skilled in the art that the examples are only for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Some of the raw material information used in the following examples is as follows:
[0061] The phenolic resin is a general-purpose phenolic resin provided by Weisi Lei New Materials Co., Ltd.
[0062] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available. The thickness of the cured molded articles in the examples and comparative examples of the present invention is 3 mm.
[0063] Example 1
[0064] This embodiment provides a phenolic resin composite material, the raw materials for preparing the composite material include the following components in weight percentage: 50% phenolic resin, 10% fumed silica, 20% aluminum oxide, 10% mica powder (the mass ratio of 300 mesh mica powder to 600 mesh mica powder is 2:1), and 10% 12 mm chopped glass fiber (with a circular cross section).
[0065] The preparation of the phenolic resin composite material includes the following preparation steps:
[0066] (1) Mixing fumed silica, aluminum oxide, and mica powder to form a uniform primary mixture;
[0067] (2) adding 12 mm chopped glass fibers to the primary mixture described in step (1) and stirring thoroughly to form a secondary mixture;
[0068] (3) adding phenolic resin to the secondary mixture described in step (2) and stirring thoroughly to ensure that the materials are evenly mixed to form a final mixture;
[0069] (4) The final mixture described in step (3) is subjected to a high-temperature curing process at 180° C. for 9 minutes and a high-pressure molding process at 8 MPa to obtain the phenolic resin composite material.
[0070] Example 2
[0071] This embodiment provides a phenolic resin composite material, the raw materials for preparing the composite material include the following components in weight percentage: 45% phenolic resin, 10% fumed silica, 25% aluminum oxide, 15% mica powder (the mass ratio of 300 mesh mica powder to 600 mesh mica powder is 1:1), and 5% 10 mm short chopped glass fiber (with a circular cross section).
[0072] The preparation of the phenolic resin composite material includes the following preparation steps:
[0073] (1) Mixing fumed silica, aluminum oxide, and mica powder to form a uniform primary mixture;
[0074] (2) adding 10 mm chopped glass fibers to the primary mixture described in step (1) and stirring thoroughly to form a secondary mixture;
[0075] (3) adding phenolic resin to the secondary mixture described in step (2) and stirring thoroughly to ensure that the materials are evenly mixed to form a final mixture;
[0076] (4) The final mixture described in step (3) is subjected to a high-temperature curing process at 150° C. for 15 minutes and a high-pressure molding process at 5 MPa to obtain the phenolic resin composite material.
[0077] Example 3
[0078] This embodiment provides a phenolic resin composite material, the raw materials for preparing the composite material include the following components in weight percentage: 55% phenolic resin, 8% fumed silica, 22% aluminum oxide, 8% mica powder (the mass ratio of 300 mesh mica powder to 600 mesh mica powder is 2:1), and 7% 12 mm chopped glass fiber (with a circular cross section).
[0079] The preparation of the phenolic resin composite material is the same as that in Example 1.
[0080] The phenolic resin composite material can still maintain excellent physical and chemical stability after being continuously exposed to a high temperature environment of 250° C. for 1000 hours.
[0081] Example 4
[0082] This embodiment provides a phenolic resin composite material, the raw materials for preparing the composite material include the following components in weight percentage: 50% phenolic resin, 12% fumed silica, 18% aluminum oxide, 12% mica powder (the mass ratio of 300 mesh mica powder to 600 mesh mica powder is 2:1), and 8% 12mm chopped glass fiber (with a circular cross section).
[0083] The preparation of the phenolic resin composite material is the same as that in Example 1.
[0084] Example 5
[0085] This embodiment provides a phenolic resin composite material, which differs from Example 1 only in that the content of mica powder is adjusted from 10% to 16%, and the increased content is reduced proportionally by other components. Other raw materials and preparation methods are the same as those in Example 1.
[0086] Example 6
[0087] This embodiment provides a phenolic resin composite material, which differs from Example 1 only in that the content of mica powder is adjusted from 10% to 4%, and the reduced content is distributed to other components in proportion. Other raw materials and preparation methods are the same as those in Example 1.
[0088] Example 7
[0089] This embodiment provides a phenolic resin composite material, which differs from Example 1 in that the content of fumed silica is adjusted from 10% to 13%, and the content of aluminum oxide is adjusted from 20% to 17%. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0090] Example 8
[0091] This embodiment provides a phenolic resin composite material, which differs from Example 1 in that the content of fumed silica is adjusted from 10% to 12%, and the content of aluminum oxide is adjusted from 20% to 18%. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0092] Example 9
[0093] This embodiment provides a phenolic resin composite material, which differs from Example 1 in that the content of fumed silica is adjusted from 10% to 7.5%, and the content of aluminum oxide is adjusted from 20% to 22.5%. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0094] Example 10
[0095] This embodiment provides a phenolic resin composite material, which differs from Example 1 in that the content of fumed silica is adjusted from 10% to 7%, and the content of aluminum oxide is adjusted from 20% to 23%. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0096] Example 11
[0097] This embodiment provides a phenolic resin composite material, which differs from Example 1 in that the content of fumed silica is adjusted from 10% to 4%, and the content of aluminum oxide is adjusted from 20% to 26%. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0098] Example 12
[0099] This embodiment provides a phenolic resin composite material, which differs from Example 1 only in that the mica powder (the mass ratio of 300 mesh mica powder to 600 mesh mica powder is 2:1) is replaced with 300 mesh mica powder, and the mica powder content is kept unchanged. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0100] Example 13
[0101] This embodiment provides a phenolic resin composite material, which differs from Example 1 only in that the 12 mm chopped glass fiber is replaced with 25 mm chopped glass fiber (commonly available on the market), and other raw materials, contents and preparation methods are the same as those in Example 1.
[0102] Example 14
[0103] This embodiment provides a phenolic resin composite material, which differs from Example 1 only in that the 12 mm chopped glass fiber with a circular cross section is replaced with the 12 mm chopped glass fiber with a square cross section. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0104] Comparative Example 1
[0105] This comparative example provides a phenolic resin composite material, which differs from Example 1 only in that fumed silica is not added and its reduced content is distributed to aluminum oxide. Other raw materials, contents and preparation methods are the same as those in Example 1.
[0106] Comparative Example 2
[0107] This comparative example provides a phenolic resin composite material, which differs from Example 1 only in that aluminum oxide is replaced by aluminum hydroxide, and other raw materials and preparation methods are the same as those in Example 1.
[0108] Comparative Example 3
[0109] This comparative example provides a phenolic resin composite material, which differs from Example 1 only in that mica powder is not added, and the reduced content thereof is proportionally distributed to other components. Other raw materials and preparation methods are the same as those in Example 1.
[0110] The phenolic resin composite materials provided in Examples 1-14 and Comparative Examples 1-3 were subjected to performance tests using the following methods:
[0111] (1) Fire performance test: The phenolic resin composite material was clamped on a conventional iron frame and tested using the vertical combustion method. The temperature was set at 800℃, 1000℃, and 1200℃. After the test at 1200℃, the apparent detection results were as follows: no burn-through > fine cracks > small cracks > cracks > fine pores > pores > cracking.
[0112] (2) Pressure bearing effect under high temperature: Three pieces of phenolic resin composite materials with dimensions of 20 mm × 20 mm × 3 mm were placed on the testing instrument for parallel experimental testing. The test temperature was 400 °C and the pressure was 12 MPa. The states of the phenolic resin composite materials after the test were compared. The strength after the test was ranked as complete > with small deformation > with small cracks > with large cracks > with gaps > with cracks > with cracks.
[0113] (3) Electrolyte resistance effect: A piece of phenolic resin composite material with a size of 20 mm × 20 mm × 3 mm was taken and directly immersed in the electrolyte (purchased from Ningbo Pobai Technology Co., Ltd.) for 7 days.
[0114] (4) Molding fluidity test: 30 g of the phenolic resin composite material was taken to test whether it could fill the mold with a longitudinal diameter of 15 mm.
[0115] The test results are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] In Table 1, "Y" means no penetration and no visible smoke, and "N" means penetration and cracking.
[0120] The test results show that:
[0121] (1) It can be seen from Examples 1 to 14 that the present invention can optimize the selection of raw materials for preparing the phenolic resin composite material, so that it has excellent heat resistance and fire resistance, can withstand 1200°C flame ablation, and will not have problems such as cracking and deforming, that is, it can effectively isolate the impact of flames; and can remain stable at a high temperature of 400°C and a pressure of 12MPa without cracking; at the same time, it can still maintain excellent physical and chemical stability after continuous exposure to a high temperature environment of 250°C for 1000h.
[0122] (2) By comparing Example 1 with Examples 5 and 6, it can be seen that the fire resistance of the obtained phenolic resin composite material can be improved by further limiting the content of mica powder in the present invention.
[0123] (3) By comparing Example 1 with Examples 7-10, it can be seen that the high-temperature pressure-bearing properties of the phenolic resin composite materials obtained in Examples 7 and 10 are both deteriorated, indicating that when the mass ratio of fumed silica to alumina is higher or lower than the preferred range of 1:(1.5-3), the high-temperature and high-pressure resistance of the obtained phenolic resin composite materials will be reduced.
[0124] (4) By comparing Example 1 with Example 11, it can be seen that Example 11 cracked during the fire resistance test at 800°C, and there were pores in the surface appearance test at 1200°C, indicating that the present invention can reduce the porosity of the obtained phenolic resin composite material by further limiting the content of fumed silica, while reducing the cracking problem caused by stress concentration and making the material easy to prepare.
[0125] (5) By comparing Example 1 with Example 12, it can be seen that the phenolic resin composite material obtained in Example 12 has cracks in the high-temperature pressure bearing capacity test, indicating that the specific mixed mica powder of the present invention can improve its dispersibility. The phenolic resin composite material obtained in Example 3 improves its high-temperature pressure bearing capacity while maintaining good fire resistance.
[0126] (6) By comparing Example 1 with Example 13, it can be seen that the length of the chopped glass fibers in Example 13 is 25 mm, and its molding fluidity is reduced, and the mold cannot be fully filled, thereby affecting the yield of the obtained product. This shows that the selection of chopped glass fibers of a specific length can significantly improve the yield of the obtained phenolic resin composite material, thereby improving its comprehensive application performance.
[0127] (7) By comparing Example 1 with Example 14, it can be seen that the cross-section of the chopped glass fiber in Example 14 is square, which has better high-temperature pressure-bearing effect, indicating that the present invention can obtain a phenolic resin composite material with better high-temperature and high-pressure resistance by further optimizing the cross-section of the chopped glass fiber.
[0128] (8) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that in Comparative Example 1, only a single component of aluminum oxide is added, and the high-temperature pressure-bearing performance of the phenolic resin composite material obtained is significantly reduced. In Comparative Example 2, the specific component aluminum oxide in the present invention is not selected, and the high-temperature pressure-bearing performance of the phenolic resin composite material obtained is also poor, and its surface layer dissolves to a certain extent in the electrolyte, that is, the electrolyte resistance is poor. This shows that the fumed silica and aluminum oxide in the present invention can play a synergistic role, thereby significantly improving the high-temperature and high-pressure resistance of the phenolic resin composite material.
[0129] (9) By comparing Example 1 with Comparative Example 3, it can be seen that when the raw materials for preparing the phenolic resin composite material do not contain mica powder, its fire resistance and high temperature resistance are both reduced.
[0130] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A phenolic resin composite material, characterized in that: The raw materials for preparing the phenolic resin composite material include phenolic resin, fumed silica, aluminum oxide, mica powder and reinforcing fiber.
2. The phenolic resin composite material according to claim 1, characterized in that Taking the total mass percentage of the raw materials as 100%, the mass percentage of the phenolic resin is 45-55%.
3. The phenolic resin composite material according to claim 1 or 2, characterized in that The fumed silica is hydrophobic fumed silica; Preferably, based on the total mass percentage of the raw materials being 100%, the mass percentage of the fumed silicon dioxide is 5-15%.
4. The phenolic resin composite material according to any one of claims 1 to 3, characterized in that The mass percentage of the aluminum oxide is 10-25% based on the total mass percentage of the raw materials for preparation being 100%; Preferably, the mass ratio of the fumed silica to alumina is 1:(1.5-3).
5. The phenolic resin composite material according to any one of claims 1 to 4, characterized in that: The mica powder is a mixture of 300-mesh mica powder and 600-mesh mica powder; Preferably, the mass ratio of 300 mesh mica powder to 600 mesh mica powder in the mixed mica powder is (1-2):(0.5-1); Preferably, based on the total mass percentage of the raw materials being 100%, the mass percentage of the mica powder is 5-15%.
6. The phenolic resin composite material according to any one of claims 1 to 5, characterized in that: The reinforcing fibers include glass fibers; Preferably, the length of the glass fiber is 10-15 mm; Preferably, the cross-section of the glass fiber includes a circle and / or a square; Preferably, based on the total mass percentage of the raw materials being 100%, the mass percentage of the reinforcing fibers is 5-10%.
7. A method for preparing a phenolic resin composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The phenolic resin composite material is obtained by mixing phenolic resin, fumed silica, aluminum oxide, mica powder and reinforcing fiber, curing and molding.
8. The method for preparing the phenolic resin composite material according to claim 7, wherein: The mixing is carried out under stirring; Preferably, the mixing comprises first mixing fumed silica, alumina and mica powder, then adding reinforcing fibers and mixing, and finally adding phenolic resin and mixing; Preferably, the curing method includes high temperature curing; Preferably, the curing temperature is 150-200°C; Preferably, the forming method includes compression molding; Preferably, the molding pressure is 5-10 MPa.
9. A battery pack housing, characterized in that: The battery pack casing comprises the phenolic resin composite material according to any one of claims 1 to 6.
10. Use of the phenolic resin composite material according to any one of claims 1 to 6 in high temperature and high pressure resistant equipment; Preferably, the high temperature and high pressure resistant equipment includes equipment in the fields of oil drilling, geothermal wells, aerospace, automobile manufacturing or high-end electronics.
Citation Information
Patent Citations
Heat-resistant high-strength phenolic molding plastic
CN109486098A
Modified phenolic molding compound with high bending strength and preparation method of modified phenolic molding compound
CN110157145A